To what extent is the use of human enhancements defended in international human rights legislation?. (December 2013) - Lawrence, David R.
Human enhancement technologies appear to come under the protection of human rights law. This protection is afforded both explicitly and through deeper analysis of the principles espoused in documents such as the Oviedo Convention and the International Bill of Human Rights, specifically its subsidiary legislation in the Universal Declaration of Human Rights and the International Convention on Economic, Social, and Cultural Rights. Focus lies on the rights to health and access to science. These can be described as rights of 'enablement', which relate to the practice of self-realisation, legislatively backed through rights to personality, personhood and self-determination. In this paper I will argue that human enhancements can act as the means by which these rights are given effect. Denied these means, one is denied the exercise of personhood. I propose, too, that the enablement provided by enhancement technology is required for true societal equality and 'real freedom' through provision of opportunity.